INCOMPLETE: A Screenplay Raising Awareness Towards Postpartum Depression - Eunike Patricia Susanto; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2023)
This thesis focuses on the possibility of postpartum depression (PPD) among new moms, as well as the importance of family support in the recovery process. The study explores the physical and emotional aspects that contribute to PPD, such as exhaustion and a lack of husband support. The screenplay dives into the path of the main character, a mother who has just given birth and is experiencing postpartum depression due to fatigue and lack of support from her husband and family. She continues to struggle to make her life better through treatment, a support group, and support from her family and she begins to share her stories through social media to raise awareness.